A 140-bp-Long Palindromic Sequence Induces Double-Strand Breaks During Meiosis in the Yeast Saccharomyces cerevisiae - Dilip K. Nag; Alicia Kurst (1997)
Palindromic sequences have the potential to form hairpin or cruciform structures, which are putative substrates for several nucleases and mismatch repair enzymes. A genetic method was developed to detect such structures in vivo in the yeast Saccharomyces cerevisiae. Using this method we previously showed that short hairpin structures are poorly repaired by the mismatch repair system in S. cerevisiae. We show here that mismatches, when present in the stem of the hairpin structure, are not processed by the repair machinery, suggesting that they are treated differently than those in the interstrand base-paired duplex DNA. A 140-bp-long palindromic sequence, on the contrary, acts as a meiotic recombination hotspot by generating a site for a double-strand break, an initiator of meiotic recombination. We suggest that long palindromic sequences undergo cruciform extrusion more readily than short ones. This cruciform structure then acts as a substrate for structure-specific nucleases resulting in the formation of a double-strand break during meiosis in yeast. In addition, we show that residual repair of the short hairpin structure occurs in an MSH2-independent pathway.